PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PENGURUS IKATAN PELAJAR NAHDLATUL ULAMA (IPNU) KOTA MALANG - Hidayatul Hikmah; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aimed to examine and analyze the influence of leadership style, communication and organizational commitment on the management performance of IPNU Malang. This research is an Explanatory Research. The subject of this research is the organizer of IPNU in Malang city. The population and the sample in this study are 38 respondents. The data was collected by distributing the questionnaires and analysed by using SPSS Version 16.0. The technique used in collecting the data is by using a census method, and the technique used in testing the study is by using the Instrument Test, Normality Test, Analysis of Multiple Linear Regression, Classical Assumptions, and Hypothesis Test. Based on the results of this study, it can be concluded that partially the Leadership Style affected much to the Management Performance, as well as the Communication, but in other hand Organizational Commitment does not affect the Management Performance. Therefore Leadership Style, Communication and Organizational Commitment significantly affected the Management Performance. It means that the independent variable is feasible to explain the analyzed independent variable.Keywords: Leadership Style, Communication, Organizational Commitment to the Management Performance